The Role of Dikmas Traffic Through the Community Information Program in Preventing Motor Vehicle Traffic Accidents in the Gresik Polres Jurisdiction Area - Marantika, Boarneges Epafroditus (Police Studies Review, 2024)
One of the roles of the police in traffic issues is to carry out preemptive and preventive actions to reduce the number of accidents. This study aims to describe the implementation of traffic education activities (Dikmas Lantas) by the Traffic Directorate of Gresik District Police at the Traffic Education Unit (Unit Kamsel) to reduce traffic accidents in the Gresik District Police area. It also aims to explain the communication methods of the Gresik District Police Traffic Education Unit in conducting Dikmas Lantas activities. The study uses a qualitative research approach conducted through field research. Data sources include interviews, observations, and document studies. The results show that the Gresik District Police Traffic Education Unit conducts Dikmas Lantas to prevent traffic violations through methods aligned with the unit’s job description, which includes mentoring and educating the public on traffic safety through various programs.